The Influence of the Principal's Leadership, Work Climate, and Work Motivation on the Performance of High School Education Personnel in Malinau Regency - Bela, Yulianti; Jabar, Cepi Safruddin Abdul; La Robi, La Robi (Journal of Educational Sciences, 2025)
This study was motivated by the low performance of educational personnel in Malinau, influenced by the leadership of the principal, work climate, and work motivation. The aim was to examine the partial and simultaneous effects of principal leadership, work climate, and work motivation on the performance of high school education staff in Malinau. The research employed a quantitative correlational approach with a total sample of 34 staff members selected through total sampling. Data were collected using Likert-scale questionnaires and analyzed with simple and multiple linear regression tests along with classical assumption checks. Results indicated that principal leadership contributed 75.4%, work climate 84%, and work motivation 81.2%, with all three variables together explaining 85.7% of the variation in staff performance. The findings conclude that principal leadership, work climate, and motivation collectively have a significant effect on staff performance in Malinau. It is recommended that stakeholders focus on enhancing these factors to improve educational personnel performance.